2006
DOI: 10.1212/01.wnl.0000231138.18629.d5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of childhood migraine attacks with oral zolmitriptan and ibuprofen

Abstract: The authors conducted a double-blind, placebo-controlled, crossover study to investigate the efficacy of oral zolmitriptan in the treatment of migraine in children and adolescents. Patients (n = 32) received placebo, zolmitriptan 2.5 mg, and ibuprofen 200 to 400 mg to treat three consecutive migraine attacks. Pain relief rates after 2 hours were 28% for placebo, 62% for zolmitriptan, and 69% for ibuprofen (p < 0.05). Both drugs are well tolerated with only mild side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 9 publications
2
60
0
8
Order By: Relevance
“…Only mild side effects were reported and good tolerability was exhibited for both drugs. 69 The nasal spray formulation of zolmitriptan has also been assessed in adolescents. In a multicenter, randomized, double-blind, placebo-controlled, 2-way, 2-attack, crossover design study, Lewis et al reported that zolmitriptan NS provided fast and signifi cantly effective relief of migraine symptoms and was well tolerated in the acute treatment of adolescent migraine.…”
Section: 103mentioning
confidence: 99%
“…Only mild side effects were reported and good tolerability was exhibited for both drugs. 69 The nasal spray formulation of zolmitriptan has also been assessed in adolescents. In a multicenter, randomized, double-blind, placebo-controlled, 2-way, 2-attack, crossover design study, Lewis et al reported that zolmitriptan NS provided fast and signifi cantly effective relief of migraine symptoms and was well tolerated in the acute treatment of adolescent migraine.…”
Section: 103mentioning
confidence: 99%
“…Other triptans have also been studied in the adolescent and [12,13] were found to be effective and well tolerated in the adolescent populations studied. Frovatriptan's pharmacokinetic profile was compared between adolescents and adults [14] and found to be similar suggesting that comparable doses might be used in these younger patients compared to adults.…”
Section: Recent Updates In the Use Of Triptans In The Pediatric Populmentioning
confidence: 99%
“…Depuis, plusieurs méta-analyses [15,25,34] et études de niveau élevé [3,17,24] ont permis de publier de nouvelles recommandations. Ainsi, l'Afssaps, en 2009, a confirmé l'utilisation de l'ibuprofène et du sumatriptan : « Le traitement de la crise doit être donné précocement.…”
Section: Stratégie Thérapeutique Traitement Médicamenteux De La Criseunclassified